2007
DOI: 10.1016/j.neuroscience.2007.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of hippocampal long-term potentiation by slow increases in ethanol concentration

Abstract: To determine how acute ethanol intoxication may alter memory processing, we examined the effects of stepwise increases in ethanol on long-term potentiation (LTP) in hippocampal slices. LTP was inhibited by acute administration of 60 mM ethanol, but was readily induced if ethanol was increased gradually to 60 mM over 75 min. Administration of 2-amino-5 phosphonovalerate (APV), an Nmethyl-D-aspartate receptor antagonist, during the stepwise increase in ethanol inhibited LTP, suggesting involvement of NMDA recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…6C). Previous studies have reported LTP depression by acute ethanol treatment at the same low intoxicating concentrations used here (i.e., 33 mM; Blitzer et al, 1990;Randall et al, 1995); however, an ethanol-tolerant form of LTP mediated by intracellular Ca 21 release has also been described at CA1 synapses in response to acute incremental administration of ethanol in vitro (60 mM; Tokuda et al, 2007). Together with these studies, our findings point to the existence of multiple pathways of hippocampal LTP that differ in sensitivity to acute and chronic ethanol actions.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…6C). Previous studies have reported LTP depression by acute ethanol treatment at the same low intoxicating concentrations used here (i.e., 33 mM; Blitzer et al, 1990;Randall et al, 1995); however, an ethanol-tolerant form of LTP mediated by intracellular Ca 21 release has also been described at CA1 synapses in response to acute incremental administration of ethanol in vitro (60 mM; Tokuda et al, 2007). Together with these studies, our findings point to the existence of multiple pathways of hippocampal LTP that differ in sensitivity to acute and chronic ethanol actions.…”
Section: Discussionmentioning
confidence: 63%
“…In adult animals, the acute (Sinclair and Lo, 1986;Blitzer et al, 1990) and chronic (Durand and Carlen, 1984;Roberto et al, 2002) administration of ethanol consistently produces decrements in LTP levels at CA1 synapses in hippocampus, which is believed to reflect the ability of acute ethanol to inhibit NMDA-and/or potentiate GABA-receptor-mediated synaptic potentials (Morrisett and Swartzwelder, 1993;Schummers and Browning, 2001;Izumi et al, 2005). Ethanol-induced depression in LTP may also reflect ethanol interactions at pathways of synaptic plasticity not involving these receptors (Hendricson et al, 2003;Tokuda et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…3). An analogous study has shown that ethanol inhibits LTP formation by blocking the NMDA receptor, possibly because the cysteine residues of NR2B are sensitive to ethanol (Herin et al 2001), and leads to amnesia (Brioni et al 1989;Dildy and Leslie 1989;Tokuda et al 2007;Wirkner et al 1999). Some studies have shown that formaldehyde can spontaneously modify the cysteine residues of proteins (Metz et al 2006;Toews et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This makes it unlikely that during a bout of oral intoxication a rise to 50 mM or greater will occur within minutes even during binge consumption. Tokuda, Zorumski, & Izumi (2007) examined the effects of slower changes in ethanol concentration by increasing ethanol levels in 10 mM increments every 15 min to achieve a final level of 60 mM, a concentration that routinely blocks LTP when administered acutely. Under these circumstances, 60 mM ethanol no longer completely inhibited CA1 LTP.…”
Section: Acute Ethanol Tolerance and Synaptic Plasticitymentioning
confidence: 99%
“…Furthermore, and differing from effects of ethanol on LTD, LTP inhibition by 60 mM ethanol persists following drug washout (Izumi, Nagashima, et al, 2005c). These observations, coupled with the finding that complete NMDAR block during ethanol administration overcame acute tolerance (Tokuda et al, 2007), led to experiments examining whether complete NMDAR block during ethanol exposure could also overcome effects on LTP. Taking advantage of the prolonged block of LTP following ethanol washout and the fact that APV can be washed out rapidly, Tokuda et al (2011) found that co-administration of 60 mM ethanol with APV allowed LTP 30 min after both drugs were removed, whereas ethanol alone resulted in persistent LTP inhibition (Fig.…”
Section: Do Metaplastic Effects Contribute To Acute Ltp Inhibition?mentioning
confidence: 99%